Effect of multi-walled carbon nanotube/Porous Carbon/SiO2 on reinforcing of cement mortar matrix: Modeling studies of effective parameters - Afshari Aghajari, Amirhossein; Safarzadeh Khosrowshahi, Mobin; Akhyani, Sina; Ghiyabi, Elahe; Banna Motejadded Emrooz, Hosein; Ramezanianpour, Amir Mohammad; Maleki, Farid; Mohammadi, Hadi (Journal of Building Engineering, 2023)
The enhancement of the mechanical properties of cement composites by various nanomaterials is now a trendy subject. This study assessed the impact of three nanomaterials on the compressive and tensile strength of Portland cement mortar: biomass-derived porous carbon, MWCNT, and SiO2. These nanoparticles were developed using environmentally friendly, inexpensive technologies, and they underwent material characterization analyses using FESEM, N2 adsorption-desorption, contact angle, FTIR, XRD, and TEM. After 7 and 28 days, the compressive and tensile strength was assessed. According to the findings, among the samples, cement-SiO2 had the maximum compressive strength (19.32 MPa). The FESEM micrographs amply support the creation of the C-H-S gel and the presence of the bridge. The outcomes further showed that the nanoparticle's presence in the matrix does not significantly impact the tensile strength. SiO2-cement had the highest tensile strength, 1.45 MPa, matching the conclusions drawn from the compressive strength. Moreover, the compressive strength of cement was unaffected by the total pore volume of nanomaterials or the pore-filling mechanism of cement. Modeling (Linear regression-least square method) made it possible to predict the compressive strength for a period of 92 days and examine the influence of effective ingredients on it. Ultimately, the results indicate that porous carbon and silica can be viable alternatives for MWCNT. •The possibility of replacing much cheaper materials, such as porous carbon and SiO2, with high-cost carbon nanotubes to increase the compressive and tensile strength.•Introducing a low-cost approach for the commercial synthesis of micro-meso porous carbon and SiO2.•Examining the effects of potent virtues on compressive strength prediction for a 92-day period using the linear regression-least square method.